Analysis of Precipitable Water and Relationship with Moisture Advection in Iran - Manizheh Kianipour; Abolfazl masoodian; Hossein Asakereh (جغرافیا و توسعه, 2022)
In this study, the specific humidity, zonal, and meridional wind components data at 850 hPa and PW(PW) data of Modis Aqua for 15-year period (2002-2017) were used; Then, the days that the average amount of PW was 2 standard deviations from the mean were selected and moisture flux was calculated for these days and two days ago. The results showed when the average PW is high (July and August), southwestern parts of the Caspian Sea coasts and northwest of the country, moisture flux is maximum. The northeast and east currents, which pass through the Caspian Sea due to the low pressure in the northeast of the Caspian Sea, cause the maximum PW to occur with the transfer of moisture to the Caspian Sea and northwest. Sub Tropical high pressure over the Arabian Sea and a thermal low pressure over the southeast of Arabian Peninsula, increases moisture flux from the Arabian Sea, the Aden Gulf, the Oman Sea and the Persian Gulf to the country's southern and southwestern coasts, as a result, the amount of PW is also increased. Occasionally, currents entering to the country from the northeast and south converge on the Lut and Central Desert Plains; and increase the atmospheric moisture.Based on the results, the presence of low pressure over the western Kazakhstan and high pressure over the Arabian Sea and low pressure in eastern Arabian Peninsula, play key roles in moisture penetration into Iran and increasing atmospheric moisture.